New species and new records of Cerambycidae (Insecta, Coleoptera) from RPPN Sanctuary of Caraça, Minas Gerais, Brazil - Monné, Marcela L.; Monné, Miguel A. (Zootaxa, 2017)
A new species of Hemilophini, Adesmus lauropalui sp. nov. and a list of species of Cerambycidae from the Reserva Particular de Patrimonio Natural (RPPN) Sanctuary of Caraça are presented. The data are based on fieldwork and the MNRJ collection. Two hundred fifty-four species of Cerambycidae are recorded, of which 158 are new distribution records.